GIS based surveillance of road traffic accidents (rta) risk for Rawalpindi city: a geo-statistical approach - Amna Butt; Sheikh Saeed Ahmad; Rabia Shabbir; Summra Erum (Kuwait Journal of Science)
Identification of previously existing traffic accident hotspots is the first step to ensure future road safety. The present study focused on providing GIS based geo-statistical surveillance for the Road Traffic Accidents (RTA) in Rawalpindi for five years (2009-2013) to determine the high risk areas or hotspots. For this purpose, spatial autocorrelation (Moran’s I test), Standard Deviational Ellipse (SDE) and hotspot (Getis-Ord Gi*) analyses were performed on the data obtained from Punjab Emergency Service Department (Rescue 1122). Spatial clusters and hotspots identified during the research lied mostly in the northern and northeastern part of the study area encompassing both commercial and residential areas of the city with majority of accident hotspots being near schools, hospitals, airport and highways. The study proposed that serious steps should be taken to improve the road safety conditions in these areas and focus of Emergency Response Providers (ERPs) should be directed there. Furthermore, the integration of GIS based expertise in the Emergency department should be ensured for regular surveillance of shifts in hotspots.